The novel 22 bp insertion mutation in a promoter region of the PITX2 gene is associated with litter size and growth traits in goats - H. Yan (Archives Animal Breeding, 2018)
The paired-like homeodomain 2 (PITX2) gene plays a critical role in regulating development, reproduction, and growth traits in ruminants. Hence, the objective of this study was to explore the polymorphisms of this gene and to evaluate their associations with quantitative traits. Herein, a novel insertion in the promoter region of the PITX2 gene was reported in Shaanbei white cashmere (SBWC) goats (n = 1012). The genotype distributions between mothers of single-kid and multi-kid groups within SBWC goats were significantly different (P < 0.01), implying that this indel mutation might affect the litter size. Furthermore, association analysis found that this indel mutation was significantly associated with litter size (P = 0.001). Individuals with genotype DD had a significantly smaller litter size than those with other genotypes (P < 0.01). Besides, this indel was significantly associated with the body length (P = 0.042) and the chest width (P = 0.031). Especially, the individuals with genotype DD had a significantly lower body length than those with genotype II (P < 0.05), which was consistent with the trend in litter size. These findings suggested that the new 22 bp indel mutation within the PITX2 gene is significantly associated with litter size and growth traits; this can be utilized as a functional molecular marker in goat breeding.